IN VITRO ANTITUBERCULOUS ACTIVITY OF OFLOXACIN AND LEVOFLOXACIN AGAINST MULTIDRUG-RESISTANT TUBERCULOSIS AND CLINICAL OUTCOMES - TADA, Atsuhiko; SODA, Ryo; TAKAHASHI, Kiyoshi; TAKAHASHI, Shuji; SHIBAYAMA, Takuo; OKADA, Chiharu; KIMURA, Goro; TAKEUCHI, Makoto; HIRANO, Atsushi; KAWAT, Noriko (Kekkaku, 2006)
[Objective] To investigate in vitro antituberculous activity of ofloxacin (OFLX) and levofloxacin (LVFX) against multidrug-resistant tuberculosis and to study the clinical out comes. [Subjects and Methods] in vitro antituberculous activity of OFLX and LVFX against multidrug-resistant strains of Mycobacterium tuberculosis isolated from 46 patients with pulmonary tuberculosis and a retropective clinical analysis of 45 patients were investigated. [Results] In su sceptibility testing, resistance rates to OFLX or LVFX were higher in intractable cases (7/20: 35 %) and in cases with prior chemotherapy using new quinolones (5/12: 42 % ). Sputum culture conversion was observed in 34 patients (76%), however 9 among them later reverted to positive culture. In a single variate proportional hazards model, risk factors related to poor outcomes (treatment failure or relapse) were resistance to OFLX or LVFX, advanced disease on chest radiograph, and the number of susceptible drugs four or less. In a multiple variate proportional hazards model, a risk factor was resistance to OFLX or LVFX. Eighteen patients (40%) died, and among them, 10 died of tuberculosis. Survival time of treatment failure patients was significantly shorter than patients with sputum culture conversion. [Conclusion] Resistance to OFLX or LVFX was considered to be a risk factor related to treatment failure and relapse in multidrug-resistant tuberculosis.